Simulation of Implant Impingement After Spinal Corrective Fusion Surgery in Patients with Previous Total Hip Arthroplasty: A Retrospective Case Series. Issue 8 (15th April 2021) - Yamato, Yu; Furuhashi, Hiroki; Hasegawa, Tomohiko; Yoshida, Go; Yasuda, Tatsuya; Banno, Tomohiro; Oe, Shin; Arima, Hideyuki; Shimizu, Yuta; Hoshino, Hironobu; Matsuyama, Yukihiro
Abstract : Study Design: A retrospective case series. Objective: The aim of this study was to introduce the prevention of total hip arthroplasty (THA) dislocation using an implant impingement simulation after spinal corrective fusion and to verify the outcomes. Summary of Background Data: A high dislocation rate was found among patients who underwent spinal deformity corrective fusion with previous THA. To avoid dislocation, an appropriate position of the stem and cup is important, but the pelvic inclination may change after corrective fusion for spinal deformity. Methods: Twelve consecutive patients (two men, 10 women; average age, 72.1 [range, 55–81] years during spine surgery) with previous THA were included. Data were retrospectively retrieved from a single-center's prospectively collected database of adult spinal deformity operation. Before surgery, anterior implant impingement simulation in THA was performed using computed tomography-based software. The tolerable pelvic tilt (PT) in which the anterior implant impingement occurred in the hip at the 120° flexion position was measured. The lumbar lordosis angle was deliberately reduced during spinal surgery according to the tolerable PT. The effect of the implant impingement simulation was verified by comparison with patients who underwent surgery before simulation (before 2014). Results: THA dislocation occurred in six patients: four of five (80%) in the non-simulation, and two of seven (28.6%) in the simulation group. The difference between the preoperative and tolerable PT angles was−25° to 33°, and three patients had negative angles. In these three patients, the risk of anterior impingement and THA dislocation significantly increased with correction of lumbar lordosis if the PT was anterior. Two patients experienced repeated THA dislocation with postoperative and tolerable PT angle differences of 2° and −23° Conclusion: Our simulation of anterior implant impingement and subsequent adjustment of the degree of spinal correction was useful to prevent dislocation. However, this method did not prevent dislocation in some patients. Level of Evidence: 4 Abstract : Seven patients with previoustal hip arthroplasty (THA) and severe adult spinal deformity underwent simulation of implant impingement to avoid postoperative THA dislocation. However, THA dislocation occurred in six patients, four (80%) non-simulation and two (28.6%) simulation patients, after spinal corrective fusion surgery.